ATMIN Is Required for Maintenance of Genomic Stability and Suppression of B Cell Lymphoma - Loizou, Joanna I. (Cancer Cell, 2011)
Defective V(D)J rearrangement of immunoglobulin heavy or light chain (IgH or IgL) or class switch recombination (CSR) can initiate chromosomal translocations. The DNA-damage kinase ATM is required for the suppression of chromosomal translocations but ATM regulation is incompletely understood. Here, we show that mice lacking the ATM cofactor ATMIN in B cells (ATMIN(ΔB/ΔB)) have impaired ATM signaling and develop B cell lymphomas. Notably, ATMIN(ΔB/ΔB) cells exhibited defective peripheral V(D)J rearrangement and CSR, resulting in translocations involving the Igh and Igl loci, indicating that ATMIN is required for efficient repair of DNA breaks generated during somatic recombination. Thus, our results identify a role for ATMIN in regulating the maintenance of genomic stability and tumor suppression in B cells.